Porous silicon-carbon negative electrode material and preparation method thereof

CN123017940APending Publication Date: 2026-10-30INNER MONGOLIA KAICHUAN NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611314016.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]为了克服上述背景技术中多孔硅在充放电过程中体积变化明显、表面界面活性较高、与碳材料之间的界面结合稳定性不足以及长期循环过程中容量容易衰减的技术难题,本发明的目的在于提供一种多孔硅碳负极材料及其制备方法

Benefits of technology

本发明采用柠檬酸和聚乙烯吡咯烷酮对多孔硅进行协同改性,柠檬酸中的羧基和羟基能够与多孔硅表面的含氧基团产生较强的界面作用,对多孔硅表面状态进行调控,同时聚乙烯吡咯烷酮能够依靠其良好的分散和成膜特性均匀分布于多孔硅表面及部分孔道,在后续惰性气氛热处理过程中进一步转化形成含氮碳质保护层;柠檬酸的界面调控作用与聚乙烯吡咯烷酮形成的碳质保护结构相互配合,使所得改性层与多孔硅具有较好的界面结合稳定性,并能够减少多孔硅活性表面与电解液的直接接触,抑制充放电过程中界面副反应及固体电解质界面膜的反复破裂和再生,同时多孔硅自身的孔隙能够为硅嵌锂产生的体积变化提供缓冲空间,从而降低颗粒开裂和粉化程度,使多孔硅在反复嵌锂、脱锂过程中保持较为稳定的结构和导电接触,进而提高多孔硅碳负极材料的首次库仑效率、可逆比容量及长期循环容量保持率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017940A_ABST
    Figure CN123017940A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of lithium ion battery negative electrode materials, and specifically discloses a porous silicon-carbon negative electrode material and a preparation method thereof. The porous silicon-carbon negative electrode material comprises synergistically modified porous silicon, artificial graphite, pitch and conductive carbon black, wherein the synergistically modified porous silicon is prepared by synergistically modifying porous silicon with citric acid and polyvinylpyrrolidone. During preparation, the interface of the porous silicon surface is regulated by citric acid, and a stable carbon protective structure is formed by utilizing the dispersion, film formation and pyrolytic carbonization of polyvinylpyrrolidone, and then the structure is combined with artificial graphite and conductive carbon black, and then the porous silicon-carbon negative electrode material is obtained through pitch coating, carbonization, crushing, shaping, screening and magnetic removal treatment. The application can improve the interface stability of the porous silicon, relieve the volume change and particle pulverization in the charging and discharging process, reduce the interface charge transfer resistance, and improve the first coulomb efficiency, rate performance and cycle stability of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery anode material technology, specifically relating to a porous silicon-carbon anode material and its preparation method. Background Technology

[0002] Lithium-ion batteries are characterized by high energy density, long cycle life, and low self-discharge rate, and are widely used in new energy vehicles, consumer electronics, and energy storage. As a crucial component of lithium-ion batteries, the anode material's specific capacity, initial coulombic efficiency, cycle stability, and rate performance directly affect the overall performance of the battery. Currently, graphite anode materials are widely used due to their structural stability, good conductivity, long cycle life, and mature manufacturing processes. However, graphite's theoretical specific capacity is relatively limited, making it difficult to meet the demands of further development of high-energy-density lithium-ion batteries. Therefore, developing anode materials with both high specific capacity and good cycle stability is of great significance.

[0003] Silicon possesses high theoretical specific capacity, low lithium intercalation potential, and abundant resource reserves, making it considered one of the most promising next-generation lithium-ion battery anode materials. However, silicon undergoes significant volume changes during charge and discharge. Repeated lithium intercalation and deintercalation can easily cause silicon particles to crack, pulverize, and lose effective contact with the conductive network. Simultaneously, the solid electrolyte interface film on the particle surface is prone to repeated rupture and regeneration, resulting in continuous consumption of active lithium and electrolyte. This leads to a decrease in the material's initial coulombic efficiency and cycle capacity decay, limiting the practical application of silicon anode materials.

[0004] To address the aforementioned issues, existing technologies typically employ methods such as silicon-carbon composites, porous structure construction, surface carbon coating, and silicon-graphite composites to improve the structural stability of silicon-based anode materials. Among these, the pores within porous silicon provide a buffer for the volume expansion of silicon during lithium intercalation. Composites of porous silicon with artificial graphite utilize graphite's excellent conductivity and structural stability to improve the overall material performance. Further surface coating and carbonization using common carbon sources such as pitch can form a carbonaceous coating layer on the surface of the composite particles, reducing direct contact between silicon and the electrolyte. Therefore, porous silicon, graphite composites, and carbon coating have become important technical means to improve the performance of silicon-based anodes.

[0005] However, existing porous silicon-carbon anode materials still have certain shortcomings. On the one hand, although the porous structure can alleviate the volume change of silicon materials, porous silicon has high surface and interfacial activity, which can easily increase side reactions with the electrolyte. On the other hand, simply mechanically combining porous silicon with graphite or using ordinary carbon sources for external coating has limited effect on the regulation of the porous silicon's own surface interface. During long-term charge and discharge, the stability of the interface between silicon particles and the carbon conductive network may still decrease. Therefore, while maintaining the relatively simple preparation process, readily available raw materials, and suitability for industrial production of existing silicon-carbon anode materials, how to further improve the surface interface state of porous silicon, enhance the bonding stability between porous silicon and carbon materials, and take into account the specific capacity, initial coulombic efficiency, and cycle stability of the material, remains a technical problem to be solved in this field. Summary of the Invention

[0006] In order to overcome the technical difficulties in the above-mentioned background technology, such as significant volume change of porous silicon during charging and discharging, high surface interface activity, insufficient interfacial bonding stability with carbon materials, and easy capacity decay during long-term cycling, the present invention aims to provide a porous silicon-carbon anode material and its preparation method. This invention employs citric acid and polyvinylpyrrolidone (PVP) to synergistically modify porous silicon. Citric acid utilizes its carboxyl and hydroxyl groups to create an interfacial interaction with the porous silicon surface, which is beneficial for improving the surface state of the porous silicon. PVP can be uniformly distributed on the surface and in the pores of porous silicon, and forms a nitrogen-containing carbonaceous structure during subsequent heat treatment, thereby constructing a relatively stable porous silicon interfacial protective layer. Furthermore, the obtained synergistically modified porous silicon is composited with artificial graphite and conductive carbon black. The artificial graphite forms a stable carbonaceous conductive framework, and asphalt is used for coating and carbonization treatment, so that a carbonaceous coating layer is formed on the surface of the composite particles. This forms a multi-level synergistic structure composed of porous silicon internal pore buffer, synergistically modified interface protection, artificial graphite conductive support, and asphalt carbonization coating. While mitigating the volume change of silicon material, it improves the interfacial bonding and conductivity between porous silicon and carbon materials, and enhances the structural stability of the material during repeated charge and discharge processes.

[0007] The objective of this invention can be achieved through the following technical solutions: A porous silicon-carbon anode material comprises the following raw materials in parts by weight: 20-45 parts of synergistically modified porous silicon; 100-160 parts of artificial graphite; 10-30 parts of pitch; and 1-5 parts of conductive carbon black; wherein the synergistically modified porous silicon is prepared by synergistic modification of porous silicon with citric acid and polyvinylpyrrolidone.

[0008] Optionally, the synergistically modified porous silica comprises the following raw materials in parts by weight: 100 parts porous silica; 5-15 parts citric acid; 2-8 parts polyvinylpyrrolidone; 20-50 parts ethanol; and 200-400 parts deionized water.

[0009] Optionally, the method for preparing synergistically modified porous silicon includes the following steps: (1) Add citric acid to deionized water, stir to dissolve, then add porous silica, and after ultrasonic dispersion and stirring, obtain porous silica dispersion; (2) Polyvinylpyrrolidone was added to ethanol, stirred and dissolved, and then added to porous silica dispersion for stirring, mixing and synergistic modification to obtain a modified mixture; (3) The modified mixture is dried, heat-treated under inert gas protection, cooled and pulverized to obtain the synergistically modified porous silicon.

[0010] Optionally, the reaction conditions in step (1) are as follows: citric acid is added to deionized water and stirred for 10 to 30 minutes at 20 to 35°C and 300 to 500 r / min until completely dissolved. After adding porous silicon, the mixture is ultrasonically dispersed at 200 to 400 W for 20 to 40 minutes, and then stirred for 1 to 3 hours at 25 to 35°C and 300 to 600 r / min.

[0011] Optionally, the reaction conditions in step (2) are as follows: add polyvinylpyrrolidone to ethanol, stir for 20 to 40 minutes at 20 to 35°C and 300 to 500 r / min until dissolved, add the obtained polyvinylpyrrolidone solution to the porous silica dispersion obtained in step (1), and stir for 4 to 8 hours at 25 to 40°C and 400 to 700 r / min.

[0012] Optionally, the reaction conditions in step (3) are as follows: the modified mixture obtained in step (2) is evaporated and concentrated at 60-80°C, and then vacuum dried at 70-90°C for 8-16 hours; the dried material is placed in an inert gas protective atmosphere and heated to 650-750°C at a heating rate of 3-5°C / min, and kept at that temperature for 1-3 hours. After the holding period, the material is naturally cooled to room temperature under inert gas protection and then pulverized.

[0013] Optionally, a method for preparing a porous silicon-carbon anode material includes the following steps: S1, premix synergistically modified porous silicon and conductive carbon black, add artificial graphite for mixing and shaping, and obtain silicon-carbon composite precursor; S2, add asphalt to the silicon-carbon composite precursor, mix and coat it to obtain coated silicon-carbon composite precursor; S3, the coated silicon-carbon composite precursor is carbonized under inert gas protection, cooled, and then crushed, shaped, sieved and demagnetized to obtain the porous silicon-carbon anode material.

[0014] Optionally, the reaction conditions for step S1 are as follows: premix the synergistically modified porous silicon and conductive carbon black at 300–500 r / min for 20–40 min, add artificial graphite and continue mixing at 300–600 r / min for 30–60 min, and then perform shaping treatment for 20–40 min to obtain the silicon-carbon composite precursor.

[0015] Optionally, the reaction conditions for step S2 are as follows: using asphalt with a softening point of 180-250℃ and a D50 particle size of 1-5μm, the asphalt and the silicon-carbon composite precursor obtained in step S1 are premixed at 300-600r / min for 20-40min, then heated to 180-260℃, and hot-mixed coating is carried out under inert gas protection for 30-90min. After coating, the mixture is cooled to room temperature.

[0016] Optionally, the reaction conditions for step S3 are as follows: under a nitrogen or argon protective atmosphere, the temperature is increased to 850-1000℃ at a heating rate of 3-5℃ / min, and held at this temperature for 2-4 hours for carbonization treatment. After carbonization, the material is naturally cooled to room temperature under an inert gas protection. The carbonized product is then crushed, shaped, and sieved to obtain a D50 particle size of 10-25μm, followed by demagnetization treatment.

[0017] The beneficial effects of this invention are: This invention employs citric acid and polyvinylpyrrolidone (PVP) to synergistically modify porous silicon. The carboxyl and hydroxyl groups in citric acid can generate strong interfacial interactions with the oxygen-containing groups on the porous silicon surface, regulating the surface state of the porous silicon. Simultaneously, PPV, with its excellent dispersion and film-forming properties, can be uniformly distributed on the surface and some channels of the porous silicon, further transforming into a nitrogen-containing carbonaceous protective layer during subsequent inert atmosphere heat treatment. The interfacial regulation effect of citric acid and the carbonaceous protective structure formed by PPV works synergistically, resulting in good interfacial bonding stability between the modified layer and the porous silicon. This reduces direct contact between the active surface of the porous silicon and the electrolyte, suppressing interfacial side reactions and repeated rupture and regeneration of the solid electrolyte interfacial film during charging and discharging. Furthermore, the pores of the porous silicon itself provide a buffer space for the volume changes caused by silicon lithium intercalation, thereby reducing particle cracking and pulverization. This allows the porous silicon to maintain a relatively stable structure and conductive contact during repeated lithium intercalation and delithiation, thus improving the initial coulombic efficiency, reversible specific capacity, and long-term cycle capacity retention of the porous silicon carbon anode material. Attached Figure Description

[0018] The invention will now be further described with reference to the accompanying drawings.

[0019] Figure 1 This is a SEM image of the sample from Example 2. Detailed Implementation

[0020] The present invention will be further described below with reference to specific embodiments. However, the present invention is not limited to the following embodiments. Equivalent adjustments made without departing from the spirit and essence of the present invention should also be considered to fall within the protection scope of the present invention.

[0021] Example 1: The purpose of this example is to provide a method for preparing porous silicon-carbon anode materials using lower addition amounts of each component and lower process parameters, in order to verify that the present invention can still achieve synergistic modification of porous silicon by citric acid and polyvinylpyrrolidone under lower formulation and process conditions, and obtain porous silicon-carbon anode materials with stable carbonaceous coating structure.

[0022] S1. Weigh out 100 parts of porous silica, 5 parts of citric acid, 2 parts of polyvinylpyrrolidone, 20 parts of ethanol and 200 parts of deionized water. Five parts of citric acid were added to 200 parts of deionized water and stirred at 20°C and 300 r / min for 10 min until completely dissolved. 100 parts of porous silica were added and ultrasonically dispersed at 200 W for 20 min. Then, stirring was continued at 25°C and 300 r / min for 1 h to obtain a porous silica dispersion. Two parts of polyvinylpyrrolidone were added to 20 parts of ethanol and stirred at 20°C and 300 r / min for 20 min until dissolved. The resulting polyvinylpyrrolidone solution was added to the porous silica dispersion and stirred at 25°C and 400 r / min for 4 h to obtain a modified mixture. The modified mixture was evaporated and concentrated at 60°C and then vacuum dried at 70°C for 8 h. The dried material was placed in a nitrogen protective atmosphere and heated to 650°C at a heating rate of 3°C / min, held at that temperature for 1 h, and then naturally cooled to room temperature under nitrogen protection and pulverized to obtain synergistically modified porous silica. S2. Weigh 20 parts of the synergistically modified porous silica, 1 part of conductive carbon black, 100 parts of artificial graphite, and 10 parts of asphalt obtained in step S1. Premix the 20 parts of synergistically modified porous silica and 1 part of conductive carbon black at 300 r / min for 20 min, add 100 parts of artificial graphite, and continue mixing at 300 r / min for 30 min. Then, perform shaping treatment for 20 min to obtain a silicon-carbon composite precursor. Use asphalt with a softening point of 180℃ and a D50 particle size of 1 μm. Add 10 parts of asphalt to the obtained silicon-carbon composite precursor, premix at 300 r / min for 20 min, then heat to 180℃ and hot mix and coat under nitrogen protection for 30 min. After coating, cool to room temperature to obtain a coated silicon-carbon composite precursor. S3. The coated silicon-carbon composite precursor obtained in step S2 is placed in a nitrogen protective atmosphere and heated to 850°C at a heating rate of 3°C / min, and held at that temperature for 2 hours for carbonization treatment. After carbonization, it is naturally cooled to room temperature under nitrogen protection. The carbonized product is crushed and shaped, and sieved to make the D50 particle size of the material 10μm. Then, it is demagnetized to obtain porous silicon-carbon anode material.

[0023] Example 2: The purpose of this example is to provide a method for preparing porous silicon-carbon anode materials using the median ratio of each component and appropriate process parameters, so that the interface regulation effect of citric acid on the porous silicon surface and the dispersion, film formation and pyrolysis carbonization of polyvinylpyrrolidone can achieve a better synergistic state, while taking into account the integrity of graphite composite structure and pitch carbon coating, so as to obtain porous silicon-carbon anode materials with better comprehensive electrochemical performance.

[0024] S1. Weigh out 100 parts of porous silica, 10 parts of citric acid, 5 parts of polyvinylpyrrolidone, 35 parts of ethanol and 300 parts of deionized water. Ten parts of citric acid were added to 300 parts of deionized water and stirred at 28°C and 400 r / min for 20 min until completely dissolved. 100 parts of porous silica were added and ultrasonically dispersed at 300 W for 30 min. Then, stirring was continued at 30°C and 450 r / min for 2 h to obtain a porous silica dispersion. Five parts of polyvinylpyrrolidone were added to 35 parts of ethanol and stirred at 28°C and 400 r / min for 30 min until dissolved. The resulting polyvinylpyrrolidone solution was added to the porous silica dispersion and stirred at 32°C and 550 r / min for 6 h to obtain a modified mixture. The modified mixture was evaporated and concentrated at 70°C and then vacuum dried at 80°C for 12 h. The dried material was placed in a nitrogen protective atmosphere and heated to 700°C at a heating rate of 4°C / min, held at that temperature for 2 h, and then naturally cooled to room temperature under nitrogen protection and pulverized to obtain synergistically modified porous silica. S2. Weigh 32.5 parts of the synergistically modified porous silica, 3 parts of conductive carbon black, 130 parts of artificial graphite, and 20 parts of pitch obtained in step S1; premix 32.5 parts of synergistically modified porous silica and 3 parts of conductive carbon black at 400 r / min for 30 min, add 130 parts of artificial graphite, and continue mixing at 450 r / min for 45 min, followed by shaping treatment for 30 min to obtain a silicon-carbon composite precursor; use pitch with a softening point of 215℃ and a D50 particle size of 3μm, add 20 parts of pitch to the obtained silicon-carbon composite precursor, premix at 450 r / min for 30 min, then heat to 220℃, and hot mix and coat under nitrogen protection for 60 min, and cool to room temperature after coating to obtain a coated silicon-carbon composite precursor; S3. The coated silicon-carbon composite precursor obtained in step S2 is placed in a nitrogen protective atmosphere and heated to 925°C at a heating rate of 4°C / min, and held at that temperature for 3 hours for carbonization treatment. After carbonization, it is naturally cooled to room temperature under nitrogen protection. The carbonized product is crushed and shaped, and sieved to make the D50 particle size of the material 17.5μm. Then, it is demagnetized to obtain porous silicon-carbon anode material. Example 3: The purpose of this example is to provide a method for preparing porous silicon-carbon anode materials using higher addition amounts of each component and higher process parameters, in order to verify the applicability of the synergistic modification system of citric acid and polyvinylpyrrolidone under higher formulation and process conditions, and to verify the feasibility of preparing porous silicon-carbon anode materials under higher silicon content and carbon coating conditions.

[0025] S1. Weigh out 100 parts of porous silica, 15 parts of citric acid, 8 parts of polyvinylpyrrolidone, 50 parts of ethanol and 400 parts of deionized water. 15 parts of citric acid were added to 400 parts of deionized water and stirred at 35℃ and 500 r / min for 30 min until completely dissolved. 100 parts of porous silica were added and ultrasonically dispersed at 400 W for 40 min. Then, stirring was continued at 35℃ and 600 r / min for 3 h to obtain a porous silica dispersion. 8 parts of polyvinylpyrrolidone were added to 50 parts of ethanol and stirred at 35℃ and 500 r / min for 40 min until dissolved. The resulting polyvinylpyrrolidone solution was added to the porous silica dispersion and stirred at 40℃ and 700 r / min for 8 h to obtain a modified mixture. The modified mixture was evaporated and concentrated at 80℃, then vacuum dried at 90℃ for 16 h. The dried material was placed in a nitrogen protective atmosphere and heated to 750℃ at a heating rate of 5℃ / min, held at that temperature for 3 h, and then naturally cooled to room temperature under nitrogen protection and pulverized to obtain synergistically modified porous silica. S2. Weigh 45 parts of the synergistically modified porous silica, 5 parts of conductive carbon black, 160 parts of artificial graphite, and 30 parts of asphalt obtained in step S1. Premix the 45 parts of synergistically modified porous silica and 5 parts of conductive carbon black at 500 r / min for 40 min, add 160 parts of artificial graphite, and continue mixing at 600 r / min for 60 min. Then, perform shaping treatment for 40 min to obtain a silicon-carbon composite precursor. Use asphalt with a softening point of 250℃ and a D50 particle size of 5μm. Add 30 parts of asphalt to the obtained silicon-carbon composite precursor and premix at 600 r / min for 40 min. Then, heat to 260℃ and hot mix and coat under nitrogen protection for 90 min. After coating, cool to room temperature to obtain a coated silicon-carbon composite precursor. S3. The coated silicon-carbon composite precursor obtained in step S2 is placed in a nitrogen protective atmosphere and heated to 1000℃ at a heating rate of 5℃ / min, and held at that temperature for 4 hours for carbonization treatment. After carbonization, it is naturally cooled to room temperature under nitrogen protection. The carbonized product is crushed and shaped, and sieved to make the D50 particle size of the material 25μm. Then, it is demagnetized to obtain porous silicon-carbon anode material.

[0026] Comparative Example 1: The purpose of this comparative example is to examine the performance of the porous silicon-carbon anode material obtained by modifying porous silicon with citric acid only and without adding polyvinylpyrrolidone, so as to compare it with Example 2 and verify the synergistic modification effect of citric acid and polyvinylpyrrolidone.

[0027] S1. Weigh 100 parts of porous silica, 10 parts of citric acid, and 300 parts of deionized water. Add 10 parts of citric acid to 300 parts of deionized water and stir for 20 minutes at 28°C and 400 r / min until completely dissolved. Add 100 parts of porous silica and ultrasonically disperse at 300 W for 30 minutes. Then continue stirring at 30°C and 450 r / min for 2 hours. Continue stirring the resulting mixture at 32°C and 550 r / min for 6 hours. Evaporate and concentrate at 70°C, then vacuum dry at 80°C for 12 hours. Place the dried material in a nitrogen protective atmosphere and heat it to 700°C at a heating rate of 4°C / min. Hold at this temperature for 2 hours. Allow it to cool naturally to room temperature under nitrogen protection and then pulverize it to obtain citric acid modified porous silica.

[0028] S2. Weigh 32.5 parts of citric acid modified porous silica, 3 parts of conductive carbon black, 130 parts of artificial graphite, and 20 parts of pitch obtained in step S1. Premix 32.5 parts of citric acid modified porous silica and 3 parts of conductive carbon black at 400 r / min for 30 min, add 130 parts of artificial graphite, and continue mixing at 450 r / min for 45 min. Then, perform shaping treatment for 30 min to obtain a silicon-carbon composite precursor. Use pitch with a softening point of 215℃ and a D50 particle size of 3μm, add 20 parts of pitch to the obtained silicon-carbon composite precursor, premix at 450 r / min for 30 min, then heat to 220℃, and hot mix and coat under nitrogen protection for 60 min. After coating, cool to room temperature to obtain a coated silicon-carbon composite precursor.

[0029] S3. The coated silicon-carbon composite precursor obtained in step S2 is placed in a nitrogen protective atmosphere and heated to 925°C at a heating rate of 4°C / min, and held at that temperature for 3 hours for carbonization treatment. After carbonization, it is naturally cooled to room temperature under nitrogen protection. The carbonized product is crushed and shaped, and sieved to make the D50 particle size of the material 17.5μm. Then, it is demagnetized to obtain porous silicon-carbon anode material.

[0030] Comparative Example 2: The purpose of this comparative example is to examine the performance of porous silicon without citric acid and polyvinylpyrrolidone synergistic modification when it is used directly to prepare porous silicon-carbon anode materials, in order to compare with Example 2 and verify the necessity of citric acid and polyvinylpyrrolidone synergistic modification of porous silicon and the resulting technical effects.

[0031] S1. Weigh 100 parts of porous silicon without citric acid and polyvinylpyrrolidone synergistic modification treatment; place the porous silicon under vacuum drying at 80℃ for 12h, then heat it to 700℃ at a heating rate of 4℃ / min in a nitrogen protective atmosphere, hold it at that temperature for 2h, cool it naturally to room temperature under nitrogen protection and pulverize it to obtain the treated porous silicon.

[0032] S2. Weigh 32.5 parts of porous silica, 3 parts of conductive carbon black, 130 parts of artificial graphite, and 20 parts of pitch obtained in step S1. Premix 32.5 parts of porous silica and 3 parts of conductive carbon black at 400 r / min for 30 min, add 130 parts of artificial graphite, and continue mixing at 450 r / min for 45 min. Then, perform shaping treatment for 30 min to obtain a silicon-carbon composite precursor. Use pitch with a softening point of 215℃ and a D50 particle size of 3μm. Add 20 parts of pitch to the obtained silicon-carbon composite precursor, premix at 450 r / min for 30 min, then heat to 220℃ and hot mix and coat under nitrogen protection for 60 min. After coating, cool to room temperature to obtain a coated silicon-carbon composite precursor.

[0033] S3. The coated silicon-carbon composite precursor obtained in step S2 is placed in a nitrogen protective atmosphere and heated to 925°C at a heating rate of 4°C / min, and held at that temperature for 3 hours for carbonization treatment. After carbonization, it is naturally cooled to room temperature under nitrogen protection. The carbonized product is crushed and shaped, and sieved to make the D50 particle size of the material 17.5μm. Then, it is demagnetized to obtain porous silicon-carbon anode material.

[0034] Performance testing: 1. First Coulomb Efficiency Test Porous silicon-carbon anode materials prepared in Examples 1-3 and Comparative Examples 1-2 were used as active materials, mixed with conductive agent SuperP and binder in the same mass ratio, and an appropriate amount of deionized water was added to form a uniform slurry. The slurry was coated on the surface of copper foil, and after vacuum drying, rolling and stamping, it was made into a working electrode. A CR2032 coin cell was assembled in an argon-filled glove box using lithium metal sheets as the counter electrode and reference electrode. After the assembled battery was allowed to stand, a first constant current charge-discharge test was conducted at 25°C and a voltage range of 0.01-1.50V at a rate of 0.1C. The first lithium insertion specific capacity and the first lithium extraction specific capacity were recorded, and the first coulombic efficiency was obtained. The first coulombic efficiency was used as the evaluation index. A higher first coulombic efficiency indicates less irreversible lithium loss and better interface stability during the first charge-discharge process.

[0035] 2.300-cycle capacity retention test The working electrode was prepared and a CR2032 coin cell was assembled using the same method as the initial coulombic efficiency test. Cyclic performance was tested at 25°C and within a voltage range of 0.01–1.50 V. First, three activation cycles were performed at a 0.1C rate to allow the electrode material to reach a relatively stable state. Then, 300 constant-current charge-discharge cycles were performed continuously at a 0.5C rate. The delithiation specific capacity in the initial stable state and the delithiation specific capacity after the 300th cycle were recorded, and the capacity retention rate after 300 cycles was obtained as the evaluation index. A higher capacity retention rate after 300 cycles indicates better structural integrity and long-term cycling stability of the material during repeated lithium insertion and delithiation processes.

[0036] 3.2C Rate Capacity Retention Test Working electrodes were prepared using porous silicon-carbon anode materials obtained in Examples 1-3 and Comparative Examples 1-2, respectively, and CR2032 coin cells were assembled. Rate performance tests were conducted at 25°C and within a voltage range of 0.01–1.50 V. The cells were first activated for three cycles at 0.1C, followed by five charge-discharge cycles at 0.2C, with the average delithiation specific capacity recorded. The rates were then sequentially increased to 0.5C, 1C, and 2C, with five consecutive charge-discharge cycles at each rate. The average delithiation specific capacity of the last three cycles at 2C was recorded. The average delithiation specific capacity of the last three cycles at 0.2C was used as a benchmark to obtain the 2C rate capacity retention rate. A higher 2C rate capacity retention rate indicates that the material can maintain a higher effective lithium storage capacity under higher charge-discharge current conditions, exhibiting better electron and lithium-ion transport performance.

[0037] 4. Charge transfer resistance test Working electrodes were prepared using the porous silicon-carbon anode materials obtained in Examples 1-3 and Comparative Examples 1-2, respectively, and CR2032 coin cells were assembled. The cells were activated by three charge-discharge cycles at 0.1C at 25°C. After standing for 2 hours under the same charge state, AC impedance testing was performed using an electrochemical workstation with an AC perturbation amplitude set to 5mV and a test frequency range of 100kHz–0.01Hz. The charge transfer resistance Rct at the electrode interface was obtained by fitting the obtained Nyquist impedance spectrum using an equivalent circuit, and Rct was used as the evaluation index. A lower charge transfer resistance indicates better charge transfer kinetics at the material interface, reflecting the improved effect of the synergistic modification of citric acid and polyvinylpyrrolidone on the porous silicon interface and conductivity.

[0038] Table 1 Performance test results of porous silicon-carbon anode materials

[0039] As shown in Table 1, the porous silicon-carbon anode materials prepared in Examples 1-3 are superior to those in Comparative Examples 1-2 in terms of initial coulombic efficiency, capacity retention after 300 cycles, 2C rate capacity retention, and charge transfer resistance. This indicates that the synergistic modification of porous silicon with citric acid and polyvinylpyrrolidone can effectively improve the interfacial stability and electrochemical performance of the porous silicon-carbon anode materials. Among them, Example 2 achieved an initial coulombic efficiency of 91.3%, a capacity retention after 300 cycles of 91.6%, a 2C rate capacity retention of 84.2%, and a charge transfer resistance of only 35.8 Ω, demonstrating the best overall performance. Examples 1 and 3 showed initial coulombic efficiencies of 88.6% and 89.7%, respectively, capacity retention after 300 cycles of 86.8% and 88.4%, respectively, and 2C rate capacity retention of 78.5% and 80.6%, respectively, also exhibiting good overall electrochemical performance. This demonstrates that the component ratios and preparation process range defined in this invention have good applicability.

[0040] Analysis of the initial coulombic efficiency showed that Example 2 achieved 91.3%, significantly higher than Comparative Example 1's 86.1% and Comparative Example 2's 81.8%. Comparative Example 1 used only citric acid to treat porous silicon without adding polyvinylpyrrolidone, resulting in an initial coulombic efficiency 5.2 percentage points lower than Example 2. Comparative Example 2 used porous silicon without the synergistic modification of citric acid and polyvinylpyrrolidone, further reducing its initial coulombic efficiency to 81.8%. This indicates that while citric acid alone can improve the surface state of porous silicon to some extent, the modified interface formed by the synergistic effect of citric acid and polyvinylpyrrolidone is more conducive to reducing the irreversible consumption of active lithium during the initial lithium intercalation process and reducing side reactions between the active surface of porous silicon and the electrolyte, thereby improving the initial coulombic efficiency.

[0041] Analysis of capacity retention after 300 cycles showed that Example 2 achieved 91.6%, Examples 1 and 3 achieved 86.8% and 88.4%, respectively, while Comparative Examples 1 and 2 only achieved 81.7% and 71.5%, respectively. In particular, Example 2 showed a 20.1 percentage point improvement over Comparative Example 2, indicating that unmodified porous silicon is more prone to interfacial instability and capacity decay during long-term lithium insertion and extraction. While citric acid modulates the interface of the porous silicon surface, polyvinylpyrrolidone (PVP) can be more uniformly distributed on the porous silicon surface and in some pores, and forms a carbonaceous protective structure after heat treatment. This protective structure, combined with the pore buffering effect of porous silicon itself, helps to reduce particle cracking, pulverization, and conductive contact loss caused by repeated volume changes in silicon, thus exhibiting a higher long-term cycle capacity retention.

[0042] From the rate performance analysis, the 2C rate capacity retention rate of Example 2 was 84.2%, which was 10.6 percentage points and 19.9 percentage points higher than that of Comparative Example 1 and Comparative Example 2, respectively. Examples 1 and 3 also achieved 78.5% and 80.6%, respectively, both higher than the two comparative examples. Further analysis using electrochemical impedance spectroscopy revealed that the charge transfer resistance of Example 2 was only 35.8 Ω, significantly lower than the 55.4 Ω of Comparative Example 1 and the 78.6 Ω of Comparative Example 2. The charge transfer resistances of Examples 1 and 3 were also reduced to 46.7 Ω and 42.3 Ω, respectively. These results correspond to each other, indicating that the interface structure formed by synergistic modification can improve the effective contact between silicon particles and the carbon conductive network, reduce the interfacial charge transfer resistance, and thus enable the material to maintain a high effective capacity at higher charge and discharge rates.

[0043] The material structure can be further explained by combining scanning electron microscope (SEM) images. The provided SEM images show significant differences in particle morphology under different treatment states: some original or insufficiently shaped particles are irregularly shaped with sharp edges, and the morphology and size uniformity between particles are relatively poor; after composite shaping treatment, the particles tend to be spherical or near-spherical, with more rounded outlines and relatively uniform particle size distribution, indicating that the shaping process can effectively improve the macroscopic morphology of the composite particles. Further observation of high-magnification images reveals relatively continuous and dense surface areas on some particle surfaces, without large-scale obvious peeling or severe cracking. This is consistent with the structural design of this invention, which uses synergistic modification followed by graphite composite and asphalt coating carbonization.

[0044] Meanwhile, images from different electron imaging modes show that spherical or near-spherical composite particles maintain a certain interparticle spacing, without large-area severe sintering to form continuous blocks, which is beneficial for maintaining the dispersibility of the powder material and the subsequent electrode processing performance. Compared to irregular particles with sharp edges, the shaped and coated composite particles have a more regular external morphology, which is beneficial for improving the contact and stacking state between particles and providing a structural basis for forming a more continuous electron transport network. Therefore, the SEM observation results correspond well with the lower charge transfer resistance and better rate performance of the embodiment from the morphological perspective.

[0045] In summary, the performance of Examples 1-3 is superior to that of Comparative Examples 1-2. Among them, Example 2 exhibits the highest initial coulombic efficiency, capacity retention after 300 cycles, and 2C rate capacity retention, while also having the lowest charge transfer resistance. Combined with the more regular particle morphology and more complete surface structure observed by SEM, it can be shown that the synergistic modification of citric acid and polyvinylpyrrolidone, combined with the subsequent graphite composite and pitch coating processes, can improve the interface and composite particle structure of porous silicon, reduce the interfacial charge transfer resistance, and improve the structural stability of the material during repeated charge and discharge processes. Ultimately, the obtained porous silicon-carbon anode material has better initial charge and discharge performance, rate performance, and long-term cycle stability.

Claims

1. A porous silicon-carbon anode material, characterized in that, The raw materials include the following parts by weight: 20-45 parts of synergistically modified porous silica; 100-160 parts of artificial graphite; 10-30 parts of pitch; and 1-5 parts of conductive carbon black. The synergistically modified porous silica is prepared by synergistic modification of porous silica with citric acid and polyvinylpyrrolidone.

2. The porous silicon-carbon anode material according to claim 1, characterized in that, The synergistically modified porous silica comprises the following raw materials in parts by weight: 100 parts porous silica; 5-15 parts citric acid; 2-8 parts polyvinylpyrrolidone; 20-50 parts ethanol; and 200-400 parts deionized water.

3. A porous silicon-carbon anode material according to claim 1 or 2, characterized in that, The method for preparing the synergistically modified porous silicon includes the following steps: (1) Add citric acid to deionized water, stir to dissolve, then add porous silica, and after ultrasonic dispersion and stirring, obtain porous silica dispersion; (2) Polyvinylpyrrolidone was added to ethanol, stirred and dissolved, and then added to porous silica dispersion for stirring, mixing and synergistic modification to obtain a modified mixture; (3) The modified mixture is dried, heat-treated under inert gas protection, cooled and pulverized to obtain the synergistically modified porous silicon.

4. The porous silicon-carbon anode material according to claim 3, characterized in that, The reaction conditions for step (1) are as follows: citric acid is added to deionized water and stirred for 10 to 30 minutes at 20 to 35°C and 300 to 500 r / min until completely dissolved. After adding porous silicon, the mixture is ultrasonically dispersed at 200 to 400 W for 20 to 40 minutes, and then stirred for 1 to 3 hours at 25 to 35°C and 300 to 600 r / min.

5. The porous silicon-carbon anode material according to claim 3, characterized in that, The reaction conditions for step (2) are as follows: add polyvinylpyrrolidone to ethanol and stir for 20 to 40 minutes at 20 to 35°C and 300 to 500 r / min until dissolved. Add the resulting polyvinylpyrrolidone solution to the porous silica dispersion obtained in step (1) and stir for 4 to 8 hours at 25 to 40°C and 400 to 700 r / min.

6. The porous silicon-carbon anode material according to claim 3, characterized in that, The reaction conditions for step (3) are as follows: the modified mixture obtained in step (2) is evaporated and concentrated at 60-80°C, and then vacuum dried at 70-90°C for 8-16 hours; the dried material is placed in an inert gas protective atmosphere and heated to 650-750°C at a heating rate of 3-5°C / min, and kept at that temperature for 1-3 hours. After the holding period, the material is naturally cooled to room temperature under inert gas protection and then pulverized.

7. A method for preparing a porous silicon-carbon anode material, characterized in that, The preparation method includes the following steps: S1, premix synergistically modified porous silicon and conductive carbon black, add artificial graphite for mixing and shaping, and obtain silicon-carbon composite precursor; S2, add asphalt to the silicon-carbon composite precursor, mix and coat it to obtain coated silicon-carbon composite precursor; S3, the coated silicon-carbon composite precursor is carbonized under inert gas protection, cooled, and then crushed, shaped, sieved and demagnetized to obtain the porous silicon-carbon anode material.

8. The method for preparing a porous silicon-carbon anode material according to claim 7, characterized in that, The reaction conditions for step S1 are as follows: premixing synergistically modified porous silicon and conductive carbon black at 300-500 r / min for 20-40 min, adding artificial graphite and continuing to mix at 300-600 r / min for 30-60 min, followed by shaping treatment for 20-40 min to obtain silicon-carbon composite precursor.

9. The method for preparing a porous silicon-carbon anode material according to claim 7, characterized in that, The reaction conditions for step S2 are as follows: using asphalt with a softening point of 180-250℃ and a D50 particle size of 1-5μm, the asphalt and the silicon-carbon composite precursor obtained in step S1 are premixed at 300-600r / min for 20-40min, then heated to 180-260℃, and hot-mixed coating is carried out under inert gas protection for 30-90min. After coating, the mixture is cooled to room temperature.

10. The method for preparing a porous silicon-carbon anode material according to claim 7, characterized in that, The reaction conditions for step S3 are as follows: under a nitrogen or argon protective atmosphere, the temperature is increased to 850-1000℃ at a heating rate of 3-5℃ / min, and held at this temperature for 2-4 hours for carbonization treatment. After carbonization, the material is naturally cooled to room temperature under an inert gas protection. The carbonized product is then crushed, shaped, and sieved to obtain a D50 particle size of 10-25μm. Subsequently, a demagnetization treatment is performed.